Influence of oligofructose-enriched inulin on survival of microencapsulated Lactobacillus casei 01 and adhesive properties of synbiotic microparticles - Tanja Petreska Ivanovska; Zoran Zhivikj; Kristina Mladenovska; Lidija Petrushevska-Tozi (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2015)
Lactobacillus casei 01 was co-encapsulated with the prebiotic oligofructose-enriched inulin at different concentrations to investigate the efficiency of the prebiotic for improving the probiotic viability. Prebiotic effect on the probiotic survival under microencapsulation conditions by spray- and freeze-drying and storage stability of encapsulated living cells at 4 °C during period of 8 weeks was evaluated. Adhesiveness of L. casei 01 loaded microparticles to pig mucin was investigated in vitro to estimate the role of microencapsulation for improving the cell adhesion ability. The microparticles produced with 3% w/w oligofructose-enriched inulin showed higher initial count, while oligofructose-enriched inulin applied at 1.5% w/w resulted in better protection of L. casei 01 under storage conditions. Further, it has been observed significantly increased pig mucin binding to microparticles compared to free probiotic cells in buffer solutions simulating GI conditions, during 24 h incubation. Hence, cell microencapsulation beside enhanced viability may allow prolonged residence time of the probiotic cells in the lower intestine through excellent muco-adhesive properties of the encapsulating materials. The results suggest synbiotic chitosan-Ca-alginate microparticles as convenient delivery system capable to ensure effective cell concentration in the lower intestine where probiotic colonization is dominant.